Hepatic Encephalopathy-Associated Cerebral Vasculopathy in Acute-on-Chronic Liver Failure: Alterations on Endothelial Factor Release and Influence on Cerebrovascular Function - Caracuel, Laura; Sastre, Esther; Callejo, María; Rodrigues-Díez, Raquel; García-Redondo, Ana B.; Prieto, Isabel; Nieto, Carlos; Salaices, Mercedes; Aller, Ma Ángeles; Arias, Jaime; Blanco-Rivero, Javier (Frontiers in Physiology, 2020)
The acute-on-chronic liver failure (ACLF) is a syndrome characterized by liver decompensation, hepatic encephalopathy (HE) and high mortality. We aimed to determine the mechanisms implicated in the development of HE-associated cerebral vasculopathy in a microsurgical liver cholestasis (MHC) model of ACLF. Microsurgical liver cholestasis was induced by ligating and extracting the common bile duct and four bile ducts. Sham-operated and MHC rats were maintained for eight postoperative weeks Bradykinin-induced vasodilation was greater in middle cerebral arteries from MHC rats. Both Nω-Nitro-L-arginine methyl ester and indomethacin diminished bradykinin-induced vasodilation largely in arteries from MHC rats. Nitrite and prostaglandin (PG) F1α releases were increased, whereas thromboxane (TX) B2 was not modified in arteries from MHC. Expressions of endothelial nitric oxide synthase (eNOS), inducible NOS, and cyclooxygenase (COX) 2 were augmented, and neuronal NOS (nNOS), COX-1, PGI2 synthase, and TXA2S were unmodified. Phosphorylation was augmented for eNOS and unmodified for nNOS. Altogether, these endothelial alterations might collaborate to increase brain blood flow in HE.